Accelerated Wound Healing on Skin by Electrical Stimulation with a Bioelectric Plaster. Issue 22 (20th September 2017) - Kai, Hiroyuki; Yamauchi, Takeshi; Ogawa, Yudai; Tsubota, Ayaka; Magome, Takahiro; Miyake, Takeo; Yamasaki, Kenshi; Nishizawa, Matsuhiko
Abstract: Wound healing on skin involves cell migration and proliferation in response to endogenous electric current. External electrical stimulation by electrical equipment is used to promote these biological processes for the treatment of chronic wounds and ulcers. Miniaturization of the electrical stimulation device for wound healing on skin will make this technology more widely available. Using flexible enzymatic electrodes and stretchable hydrogel, a stretchable bioelectric plaster is fabricated with a built‐in enzymatic biofuel cell (EBFC) that fits to skin and generates ionic current along the surface of the skin by enzymatic electrochemical reactions for more than 12 h. To investigate the efficacy of the fabricated bioelectric plaster, an artificial wound is made on the back skin of a live mouse and the wound healing is observed for 7 d in the presence and absence of the ionic current of the bioelectric plaster. The time course of the wound size as well as the hematoxylin and eosin staining of the skin section reveals that the ionic current of the plaster leads to faster and smoother wound healing. The present work demonstrates a proof of concept for the electrical manipulation of biological functions by EBFCs. Abstract : Wound healing on skin is accelerated by a plaster device with a built‐in enzymatic biofuel cell that drives ionic current on the wound. Cells in the skin respond to electric current during wound healing processes. A stretchable bioelectric plaster fits to skin and generates ionic current on the wound by enzymatic electrochemical reactions to promote these processes.